2017
DOI: 10.1111/jcmm.13299
|View full text |Cite
|
Sign up to set email alerts
|

Lactuca capensis reverses memory deficits in Aβ1‐42‐induced an animal model of Alzheimer's disease

Abstract: We investigated the neuropharmacological effects of the methanolic extract from Lactuca capensis Thunb. leaves (100 and 200 mg/kg) for 21 days on memory impairment in an Alzheimer's disease (AD) rat model produced by direct intraventricular delivery of amyloid‐β1‐42 (Aβ1‐42). Behavioural assays such as Y‐maze and radial arm maze test were used for assessing memory performance. Aβ1‐42 decreased cognitive performance in the behavioural tests which were ameliorated by pre‐treatment with the methanolic extract. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 71 publications
(84 reference statements)
2
18
0
Order By: Relevance
“…In addition, the literature data [31,32] emphasizes that in patients diagnosed with Alzheimer's disease, irreversible brain disorder characterized mainly by cholinergic deficits, oxidative stress and mitochondrial dysfunctions [33], the target is to inhibit AChE activity in order to maintain acetylcholine levels in the neuronal synapses to obtain beneficial effects in patients with Alzheimer's disease [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the literature data [31,32] emphasizes that in patients diagnosed with Alzheimer's disease, irreversible brain disorder characterized mainly by cholinergic deficits, oxidative stress and mitochondrial dysfunctions [33], the target is to inhibit AChE activity in order to maintain acetylcholine levels in the neuronal synapses to obtain beneficial effects in patients with Alzheimer's disease [29].…”
Section: Resultsmentioning
confidence: 99%
“…AChE was determined using acetylcholine as an artificial substrate, by spectrophotometric method with 2dinitrobenzoic acid (DTNB) to form a yellow colored complex having a maximum absorption at the wavelength of 412 nm [29]. The enzymatic activity was expressed as nmol/min·mg protein.…”
Section: Ache Assay Activitymentioning
confidence: 99%
“…26) Each mouse was anaesthetized with sodium pentobarbital (intraperitoneal administration at a dose of 70 mg/kg, Sigma, U.S.A) and fixed in a stereotaxic apparatus (Leica, Germany). According to the atlas by Paxinos and Franklin, 27) guide cannula was implanted into the right lateral ventricle (AP = 0.5 mm, RL = 1.0 mm, DV = 2.0 mm), or were implanted in the bilateral hippocampus CA1 region (AP = 2 mm, RL=±1.5 mm, DV = 1.2 mm). Each mouse was individually housed and allowed 5-7 d to recover after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…L. indica L. is used for its antibacterial and anti-inflammatory effects. L. capensis Thunb is used for treating sores, ulcers, leprosy, eczema, and the milky latex of L. virosa L., known as "lactucarium", is taken as a sedative-hypnotic [5][6][7]. Bioactivity studies on Lactuca species have shown that these plants have analgesic, anti-inflammatory, antioxidant, anticarcinogenic, hepatoprotective, neuroprotective, antidiabetic, and anxiolytic effects [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%